Difference and sameness as modes of integration: anthropological perspectives on ethnicity and religion - Schlee, Günther; Horstmann, Alexander (Integration and conflict studies, 2018)
What does it mean to “fit in?” In this volume of essays, editors Günther Schlee and Alexander Horstmann demystify the discourse on identity, challenging common assumptions about the role of sameness and difference as the basis for inclusion and exclusion. Armed with intimate knowledge of local systems, social relationships, and the negotiation of people’s positions in the everyday politics, these essays tease out the ways in which ethnicity, religion and nationalism are used for social integration.